Gospodarka wodno-ściekowa w okresie transformacji społeczno-gospodarczej państwa na przykładzie województwa śląskiego - Rączaszek, Andrzej; Rozpondek, Patrycja; Skibiński, Andrzej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
In large agglomerations the natural ability of self-cleaning undergoes the limitation and reduction, because on the comparatively small area all phenomena of social and economic life run with enlarged intensity, and the process of formation of the pollution becomes continuous. The aim of the article is a presentation of the water economy and water sewage disposal during the period of social and econornic transformation of the country on the example of the Silesian province. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 178-185